"Developing Robust Hydrometallurgical Processes to Recover Metals from Deposits with Large Geometallurgical Variation" - J J. Eksteen; E A. Oraby; B C Tanda (The Australasian Institute of Mining and Metallurgy, 2016)
"Base metal and precious metal deposits are well known for their significant geometallurgical variation throughout the volume of the proven resource. At the metallurgical level, the plant normally processes an upper oxidised layer, a transition zone and a sulfide zone, often leading to different processing techniques for the different zones. A novel processing approach is presented whereby alkaline leaching with glycine is used to leach base and precious metals, using a copper-gold ore deposit as a case study. Glycine is a cheap, non-toxic, non-volatile, highly water-soluble crystalline solid produced industrially in bulk quantities. As a chelating ligand it forms a number of stable glycinate complexes with Ni, Co, Cu, platinum group metals (PGMs), Au, Ag, Zn, Pb, Hg and Cd, with broad stability regions over an extended temperature-pH-Eh range, allowing dissolution of these metals in the neutral and alkaline regions (pH 7–13). It has been shown that this lixiviant system can leach the metals from their oxide, oxy-halide, basic sulfate, carbonate, native and various sulfide forms, including refractory sulfides such as chalcopyrite. Extraction of the metals from their soluble glycinates is easily achieved using a range of solvent extraction and precipitation processes, and the glycine remains stable in aqueous solution for recycle and reuse. Minerals bearing metals in Groups 1 to 8 of the periodic table are normally unaltered. This technology therefore provides a highly selective leaching environment for the extraction of numerous scarce metals of economic interest, with minimal interaction with gangue minerals, whilst using environmentally benign reagents. Problematic leach residues such as jarosites, elemental sulfur and silica gels are averted through this processing approach. This technology allows hydrometallurgical processing that is much less domain-sensitive in the geometallurgical sense, and utilises essentially the same key reagents for the whole deposit.CITATION:Eksteen, J J, Oraby, E A and Tanda, B C, 2016. Developing Robust Hydrometallurgical Processes to Recover Metals from Deposits with Large Geometallurgical Variation, in Proceedings The Third AusIMM International Geometallurgy Conference (GeoMet) 2016, pp 15–20 (The Australasian Institute of Mining and Metallurgy: Melbourne)."